Editorial: Enabling technologies and business models for energy communities - Burgio, Alessandro; Jasiński, Michał; Leonowicz, Zbigniew (Frontiers in Energy Research, 2024)
This Research Topic on “Enabling Technologies and Business Models for Energy Communities” presents a comprehensive exploration of critical facets in the realm of sustainable energy transitions. The Research Topic encompasses diverse topics, ranging from smart energy frameworks for urban communities and off-grid renewable energy deployment in Mexico to the impact of institutional support on the coalbed methane industry. It further investigates complex grid investment decisions, solar-based irrigation adoption in water-scarce regions, and risk management in power supply projects. Additionally, the Research Topic delves into financial aspects, exploring the pricing of Public-Private Partnership (PPP) project Asset-backed Securities (ABS) products, the impact of managerial competence on corporate carbon performance, and equity-based predictions for the energy industry. The influence of innovation on fossil fuel abandonment in low and middle-income countries and the significance of climate risk for green innovation in heavy-polluting industries are also examined. A regional perspective is provided on the technological convergence of hydrogen energy, and the interplay between renewable energy, Gross Domestic Product (GDP), and CO2 emissions in highly-globalized countries is scrutinized. Lastly, the effects of green credit policy on the risk of stocks prices crash are investigated. Together, these contributions offer a holistic understanding of the challenges and opportunities in enabling technologies and business models for energy communities, contributing valuable insights for researchers, policymakers, and industry stakeholders striving for a sustainable energy future.